Association Between Body Mass Index and Handgrip Strength Among Obese Adult Women: A Cross-Sectional Study - Lazuardi, Yofan Izdihar; Ali , Mohammad Arif; Sugiarto, Sugiarto; Kurniawati, Dewi Marfu’ah; Putra, Arvyn Nabil Deviar; Laroibafih, Alifya Nur Muhammad; Agustina, Azkia (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Handgrip strength is an important indicator of muscle function that reflects overall physical condition. This study aimed to analyze handgrip strength and examine its relationship with Body Mass Index (BMI) in obese women. A quantitative cross-sectional design was conducted involving 36 obese women selected using purposive sampling. BMI was calculated based on body weight and height measurements, while handgrip strength was measured using a hand dynamometer. Data normality was tested using the Shapiro–Wilk test, which indicated that BMI was not normally distributed (p < 0.05). Therefore, the relationship between variables was analyzed using Spearman’s rho correlation test. The results showed that handgrip strength among obese women was generally categorized as low. The correlation analysis revealed no significant relationship between BMI and right-handgrip strength (r = −0.054; p = 0.755) or left-handgrip strength (r = −0.014; p = 0.936). The correlations were negative, very weak, and statistically insignificant. These findings suggest that variations in BMI are not associated with meaningful changes in handgrip strength within this sample. In conclusion, BMI may not be a sufficient standalone indicator to assess hand muscle strength in obese women. Therefore, direct functional measurements are recommended to obtain a more accurate evaluation of muscle strength in this population.